Ethnobotanical study of sikkam (Bischofia javanica) in Simalungun District, North Sumatra, Indonesia - RIDAHATI RAMBEY; BINTANG PANDAPOTAN PANJAITAN; SUKENDRA PURBA; ANITA ZAITUNAH; RAHMAWATY RAHMAWATY; SUTOMO SUTOMO; MUHAMMAD HADI SAPUTRA; PENIWIDIYANTI PENIWIDIYANTI; FAEZAH PARDI; MOHD NAZIP SURATMAN; MOHD HASMADI ISMAIL (Society for Indonesian Biodiversity, 2025)
Abstract. Rambey R, Panjaitan BP, Purba S, Zaitunah A, Rahmawaty, Sutomo, Saputra MH, Peniwidiyanti, Pardi F, Suratman MN, Ismail MH. 2025. Ethnobotanical study of sikkam (Bischofia javanica) in Simalungun District, North Sumatra, Indonesia. Biodiversitas 26: 2393-2401. Sikkam (Bischofia javanica) is a culturally significant plant traditionally utilized as both a medicinal resource and a culinary seasoning by the Simalungun community in North Sumatra, Indonesia. The ethnobotanical use of B. javanica was documented in this study by evaluating the utilized plant parts, associated disease treatments, methods of application and processing, traditional culinary uses, and descriptive insights into conservation knowledge and harvesting techniques of B. javanica. Quantitative ethnobotanical parameters, including Reported Use (RU) and Informant Consensus Factor (ICF), were also assessed based on information obtained from the Simalungun community in three villages: Pondok Buluh, Sipolha Harison, and Sirube Rube. Data were collected through semi-structured interviews with local knowledge holders, identified using a snowball sampling technique. The study recorded 14 traditional medicinal uses and 10 culinary applications for B. javanica. The highest ICS value for medicinal use was attributed to its role in treating diarrhea (30%), while its most significant culinary application was as a key ingredient in Dayok Nabinatur seasoning (50%). Processing methods were predominantly characterized by squeezing, with 75.13% of medicinal preparations and 100% of culinary uses relying on this technique. The presence of B. javanica in mixed agroforestry systems and community-managed landscapes, reflecting local conservation practices. These findings emphasize the cultural and practical importance of B. javanica in Simalungun communities, reflecting its role in sustaining traditional knowledge and supporting livelihoods. Promoting sustainable use and conservation of B. javanica can contribute to biodiversity preservation and the protection of intangible cultural heritage, offering pathways for its utilization beyond local communities.